Multiple Sources of Aging Attitudes: Perceptions of Age Groups and Generations From Adolescence to Old Age Across China, Germany, and the United States. (July 2020) - Weiss, David; Zhang, Xin
Emerging evidence suggests that people not only categorize themselves and others based on age but also in terms of their generational membership. This cross-cultural study compared attitudes and stereotypes toward age and generational groups across the life span in China, Germany, and the United States including 1, 112 participants between 18 and 86 years of age. We asked younger, middle-aged, and older respondents to rate either six age groups (e.g., adolescents, young adults, middle-aged adults, young-old, older, and old-old adults) or six matching generational groups (e.g., Generation Z, Millennials, Generation X, Baby Boomer, Silent Generation, and Greatest Generation) on various characteristics (e.g., happy, competent, selfish). Consistent with our hypotheses, the results demonstrate that across all three countries older generations were perceived consistently more positive, whereas older age groups were perceived as less positive. These findings suggest that generations represent a source of positive regard and high social status in later life across different countries with different historical backgrounds and cultures.